IDENTIFIKASI PATOGEN PENYEBAB BUSUK BATANG PADA BIBIT EUCALYPTUS PELLITA DI PERSEMAIAN - Iin Arsensi (Fakultas Kehutanan Universitas Mulawarman, 2018)
The pathogen attacks the host plant in various ways to obtain the food substance needed by the host pathogen. To get into the host pathogen is able to break the host's defense reaction. The aim of the study was to know the symptoms and signs of stem rot disease in E. pellita in the nursery. In addition, also to determine the frequency and intensity of rodent pathogen attack in plant seeds E. pellita from shoot cuttings. Research in the nursery begins by determining the sample of plant seeds to be observed. Seed determination is done by census. Seedlings consisted of 120 plants in a plastic rack that was repeated as many as 3 replications so that the total number of seedlings observed was 120 plant seed x 3 replicates x 4 families = 1.440 plant seeds. The pathogen that causes stem rot on E. pellita seed is Fusarium sp which is transmitted through soil.